The Protective Role of Hydrogen Sulfide Against Obesity-Associated Cellular Stress in Blood Glucose Regulation - Ania Mezouari; Radhika Nangia; Jeffrey Gagnon (MDPI AG, 2020)
Circulating palmitic acid (PA) is increased in obesity and causes metabolic stress, leading to diabetes. This includes the impairment of the glucoregulatory hormone glucagon-like peptide-1 (GLP-1) secreted from intestinal L-cells. Recently, the anti-inflammatory gasotransmitter hydrogen sulfide (H2S) has been implicated in the enhancement of GLP-1 secretion. We hypothesized that H2S can reduce the oxidative stress caused by palmitate and play a protective role in L-cell function. This study was conducted on both human and mouse L-cells and a mouse model of Western diet (WD)-induced obesity. PA-induced L-cell stress was assessed using DCF-DA. H2S was delivered using the donor GYY4137. C57BL/6 mice were fed either chow diet or PA-enriched WD for 20 weeks with ongoing measurements of glycemia and GLP-1 secretion. In both L-cell models, we demonstrated that PA caused an increase in reactive oxygen species (ROS). This ROS induction was partially blocked by the H2S administration. In mice, the WD elevated body weight in both sexes and elevated fasting blood glucose and lipid peroxidation in males. Additionally, a single GYY4137 injection improved oral glucose tolerance in WD-fed male mice and also enhanced glucose-stimulated GLP-1 release. To conclude, H2S reduces oxidative stress in GLP-1 cells and can improve glucose clearance in mice.